(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
As part of our ongoing endeavour to expand the possible mappings in Concepticon, I introduce an extended concept list of Vietnamese based on the Intercontinental Dictionary Series (IDS). The list includes elicitation glosses for 1,310 concepts that can be used as a reference to add more data or for comparative analyses. Here, I present the creation of the list and its content.